The Effect of Accountability, Transparency, and Abnormal Accrual Against Potential Corruption in Indonesia - Safira Nada Sabila; Rindu Rika Gamayuni; Saring Suhendro; Rialdi Azhar (International Journal of Economics, Commerce, and Management, 2024)
Corruption is a serious problem that has become a concern in many countries, including Indonesia. Regional governments as entities responsible for the provision of public services and the use of public budgets have an important role in efforts to prevent and reduce corruption. Corrupt practices undermine public trust in the government, hinder economic, social and political development, and result in significant financial losses for the state and society. Corruption results in huge losses for Indonesian society and the economy. Public funds that should be used for infrastructure development, education and health services are often misused or siphoned off by corrupt parties. This impact can hinder improving the quality of life of Indonesian people and the country's economic growth. The crime of corruption is defined as a violation of people's rights, therefore the crime of corruption is included in the category of extraordinary crimes, where extraordinary methods are needed to overcome them (Butt, 2017).